2008
DOI: 10.1097/aln.0b013e318173f103
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Balance of the Upper Airway and Obstructive Sleep Apnea

Abstract: Upper airway anatomical imbalance is involved in the pathogenesis of OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
128
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(137 citation statements)
references
References 32 publications
5
128
0
4
Order By: Relevance
“…3 On the other hand, it was also suggested that an unfavorable relationship between the soft tissues and the bony enclosure size represents a possible anatomically based predisposition towards OSA. [27][28][29] Based on that, the need to evaluate the skeletal features in the treatment planning phases seems to emerge. Furthermore, it is important to point out that anatomical variables depend on ethnic differences.…”
Section: Discussionmentioning
confidence: 99%
“…3 On the other hand, it was also suggested that an unfavorable relationship between the soft tissues and the bony enclosure size represents a possible anatomically based predisposition towards OSA. [27][28][29] Based on that, the need to evaluate the skeletal features in the treatment planning phases seems to emerge. Furthermore, it is important to point out that anatomical variables depend on ethnic differences.…”
Section: Discussionmentioning
confidence: 99%
“…Shott and Donnelly (2004) observed 15 young patients with Down's syndrome after tonsillectomy with persistent upper airway obstruction and found that 80% exhibited tongue glossoptosis. Tsuiki et al (2008) reported that OSAHS patients have significantly larger tongues for a given maxillomandible size than non-OSAHS subjects. However, because of technical limitations, dynamic changes in tongue shape and position during sleep are seldom reported (Shott and Donnelly, 2004;Fricke et al, 2006;Zhang et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…These results are in line with studies showing that tongue dimensions and pharyngeal length also contribute to increase the risk of upper airway collapse during sleep. 4,7,[25][26][27] In addition, a lower positioned hyoid bone is the most commonly reported cephalometric abnormality among patients with OSA. Hyoid bone position also has a close relationship with OSA severity.…”
Section: Discussionmentioning
confidence: 99%